Forensics in Telecommunications, Information, and Multimedia Third International ICST Conference, e-Forensics 2010, Shanghai, China, November 11-12, 2010, Revised Selected Papers - Lai, Xuejia; Gu, Dawu.; Jin, Bo.; Wang, Yongquan; Li, Hui.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the Third International ICST Conference on Forensic Applications and Techniques in Telecommunications, Information and Multimedia, E-Forensics 2010, held in Shanghai, China, in November 2010. The 32 revised full papers presented were carefully reviewed and selected from 42 submissions in total. These, along with 5 papers from a collocated workshop of E-Forensics Law, cover a wide range of topics including digital evidence handling, data carving, records tracing, device forensics, data tamper identification, and mobile device locating.
Keywords: Computer science; Computer Communication Networks; Operating systems (Computers).; Optical pattern recognition; Computers -- Law and legislation; Information Systems; Computer Science; Computer Communication Networks; Management of Computing and Information Systems; Legal Aspects of Computing; Computers and Society; Operating Systems; Pattern Recognition